2022
DOI: 10.1002/jcla.24263
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of hsa_circ_000839 and hsa_circ_0005986 in breast cancer

Abstract: Background Breast cancer (BC) is one of the leading causes of death among women around the world. Circular RNAs (circRNAs) are a newly discovered group of non‐coding RNAs that their roles are being investigated in BC and other cancer types. In this study, we evaluated the association of hsa_circ_0005986 and hsa_circ_000839 in tumor and adjacent normal tissues of BC patients with their clinicopathological characteristics. Materials and methods Total RNA was extracted from tumors and adjacent non‐tumor tissues b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…189 Evidence suggests that downregulated hsa_circ_000839 in patients with BC exhibits a negative correlation with BMI, but the underlying mechanism is still unclear. 190 A transcriptome study of circRNAs was conducted, focusing on obese and postmenopausal patients with EC and revealed the presence of 174 differentially expressed circRNA in EC tissues compared with adjacent normal tissues. 191 Nonetheless, additional functional research is required to determine the circRNAs that can offer diagnostic and prognostic assistance in relation to obesityrelated EC.…”
Section: Circrnas In Obesity-associated Diseasesmentioning
confidence: 99%
“…189 Evidence suggests that downregulated hsa_circ_000839 in patients with BC exhibits a negative correlation with BMI, but the underlying mechanism is still unclear. 190 A transcriptome study of circRNAs was conducted, focusing on obese and postmenopausal patients with EC and revealed the presence of 174 differentially expressed circRNA in EC tissues compared with adjacent normal tissues. 191 Nonetheless, additional functional research is required to determine the circRNAs that can offer diagnostic and prognostic assistance in relation to obesityrelated EC.…”
Section: Circrnas In Obesity-associated Diseasesmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a special class of non-coding RNA molecules that are formed by a non-canonical splicing mechanism of reverse splicing, connecting the 3' end of the exon to the 5' end of the same or upstream exon, forming a closed loop. 7 At present, domestic and foreign studies have confirmed that circRNA can participate in the occurrence and development of laryngeal squamous cell carcinoma, 8 bladder cancer, 9 breast cancer, 10 etc. In Non-Small Cell Lung Cancer (NSCLC), highly expressed circ_ZNF124 promotes the occurrence and development of NSCLC by promoting the activation of JAK2/STAT3 signaling pathway.…”
Section: Introductionmentioning
confidence: 96%
“…Tese RNAs are categorized into two groups as follows: short ncRNAs with a length <200 nucleotides and long noncoding RNAs (lncRNAs) with a length over 200 nucleotides [13]. Although most of the lncRNAs are not protein-coding, they are involved in modulation of transcription patterns and regulation of diferent protein activities [13][14][15][16]. LncRNAs have a crucial role in infammatory pathways and infammasomes [17].…”
Section: Introductionmentioning
confidence: 99%